PENGARUH SIARAN BELANJA LANGSUNG, DUKUNGAN SELEBRITI, PROMOSI, ULASAN PELANGGAN ONLINE, DAN DAYA TARIK IKLAN TERHADAP KEPUTUSAN PEMBELIAN DI ECOMMERCE (Studi pada Pengguna Lazada di Kota Semarang) - Melita, Shelli; Tri Astuti, Sri Rahayu (Faculty of Economics and Business Diponegoro University, 2024)
ABSTRACT The Covid-19 pandemic has a significant impact on various aspects of life changes to digital. Trend of online shopping using e-commerce is profitable for consumers. This condition creates opportunities and challenges for business. This platform encourages every firms to optimize digitalization as part of its marketing strategy. This study aims to investigate live streaming shopping, celebrity endorser, promotion, online customer reviews, and advertising attractiveness on purchasing decisions among Lazada users in Semarang City. This study was conducted using a quantitative approach. Data collection was carried out by distributing questionnaires. A total of 149 respondents who met the criteria were involved with non probability sampling techniques. The data that has been collected is analyzed using IBM SPSS Version 26 software. The results show that live streaming shopping, promotion, online customer reviews, and advertising attractiveness have a positive and significant effect on purchasing decisions. Meanwhile, celebrity endorsers does not have significant effect on purchasing decisions. With the acquisition of the largest coefficient of 0.324 for the effect of live streaming shopping. Lazada sellers should increase the frequency of live streaming to engage with their audience as an effective tool for boosting sales and influencing purchase decisions.